2009
DOI: 10.2166/wqrj.2009.012
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Long-Term Performance and Use of Biosand Filters in Posoltega, Nicaragua

Abstract: An evaluation was conducted in 2007 on biosand filters that were installed in Posoltega, Nicaragua in 1999 and 2004.The objectives were to characterize the condition and use of filters eight and three years after installation, determine filter performance of those filters still in use, and identify determinants of successful long-term use and performance. Methods consisted of household identification, user questionnaires, and water quality testing. Of the 234 filters installed, only 24 were found to still be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 6 publications
(7 reference statements)
3
25
0
11
Order By: Relevance
“…The study found out microbial removal effectiveness of biosand filter did not significantly differ between source water samples; KMS2, RWA1 and KMS1 ( Table 2). The present study partially supports Vanderzwaag et al (2009), who reported that average log reductions were 1.7 (98%) for total coliforms and 1.4 (96%) for Escherichia coli. Stauber et al (2011) reported that when analysis of biosand filters was restricted to samples that had higher Escherichia coli concentrations, removals greater than 99% were measured.…”
Section: Discussionsupporting
confidence: 91%
“…The study found out microbial removal effectiveness of biosand filter did not significantly differ between source water samples; KMS2, RWA1 and KMS1 ( Table 2). The present study partially supports Vanderzwaag et al (2009), who reported that average log reductions were 1.7 (98%) for total coliforms and 1.4 (96%) for Escherichia coli. Stauber et al (2011) reported that when analysis of biosand filters was restricted to samples that had higher Escherichia coli concentrations, removals greater than 99% were measured.…”
Section: Discussionsupporting
confidence: 91%
“…Figures 9 and 10 provide a summary of the reported removal efficiencies of biosand filters. Overall, the reported log removals of biosand filters for bacteria (E. coli) and viruses (mostly echovirus and bacteriophage) are between 0-3 and 0-7, respectively (Ahammed and Davra, 2011;Akvopedia, 2014c;Baumgartner et al, 2007;Duke et al, 2006;Murphy et al, 2010a;Palmateer, 1999;Sswm.info, 2014;Stauber et al, 2009;Vanderzwaag et al, 2009;Wang et al, 2014). The log removal of bacteria is centred on 0.4-2; while the distribution of log removals reported for viruses is widely scattered.…”
Section: Biosand Filtersmentioning
confidence: 99%
“…One of their recommendations is, "Education about waterborne diseases, methods of safe water storage, and methods of disinfecting the stored filtered water should accompany the installation of the filter" (p. 9). Similarly, in a study of BSF use in Nicaragua, Vanderzwaag, Atwater and Bartlett (2009) found that improper operator use contributed decreased effectiveness of the filter:…”
Section: Education and Training Of Pou Water Systemsmentioning
confidence: 96%
“…The researchers found only 10% of the filters were still in use after 8 years. Of those still being used they averaged a reduction of 98% total coliforms (Vanderzwaag et al, 2009). The researchers suggested the low use rate was a result of a failure of implementation and specifically the cracking of the earlier concrete filters.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation